Social vulnerability shapes deep clinical phenotypes and brain health in aging and dementia across Latin America - Farombi, Temitope; Azzi, Tiago; Legaz, Agustina; Aguillón, David; Avila‐Funes, José Alberto; BEHRENS PELLEGRINO, MARIA ISABEL; Bruno, Martín; Cardona, Juan Felipe; Custodio, Nilton; Delgado, Carolina; Pina‐Escudero, Stefanie; Galofre, Maria del Pilar Garavito; et al. (Wiley, 2026)
INTRODUCTION Adverse social conditions across the life course influence brain aging and dementia, yet their compounded impact on clinical phenotypes remains underexplored, particularly in Latin America, where social inequality and dementia burden are high. METHODS We studied 3941 individuals from six Latin American countries, including cognitively unimpaired controls (CU), Alzheimer's disease (AD), and frontotemporal lobar degeneration (FTLD). A life‐course questionnaire captured eight domains of social vulnerability, used to derive a social vulnerability index and latent vulnerability profiles. Brain health was characterized across 37 cognitive, functional, mental health, and dementia severity indicators. RESULTS Higher vulnerability was mostly associated with executive and memory deficits in CU, cognitive and functional impairment in AD, and social cognition and neuropsychiatric symptoms in FTLD. Multidimensional brain health was affected across groups. DISCUSSION Compounded social vulnerability is a key determinant of clinical expression in aging and dementia, underscoring the need for life‐course–informed and equity‐oriented dementia models.